A Scientific Discovery in Virtual Reality and Augmented Reality Enriched with Artificial Intelligence - Karabatak, Murat; Ay, Sevinc; Karabatak, Songul (Institute of Electrical and Electronics Engineers Inc., 2025)
Artificial Intelligence (AI) powered Virtual Reality (VR) and Augmented Reality (AR) technologies enrich the user experience by providing innovative solutions in a wide range of fields such as education, healthcare, gaming, architecture and tourism. While VR provides users with an interactive experience in a fully digital universe, AR uses physical and virtual elements simultaneously by overlaying digital objects or information on the real world. Artificial intelligence algorithms make it possible for these environments to become more realistic, dynamic and personalized. In this bibliometric analysis study, scientific publications in the fields of artificial intelligence (AI)-assisted virtual reality (VR) and augmented reality (AR) were comprehensively analyzed. By revealing the citation densities, author profile analysis, and cross-country collaboration networks of 476 articles obtained from the Web of Science (WoS) database, the study demonstrated that the topic is a rapidly growing area in the academic literature that encourages interdisciplinary collaborations. VOSwiever (version 1.6.20), R studio (2024.12.1) Bibliometrix package and Gephi (0.10.1) were used for bibliometric analysis. © 2025 IEEE.
13th International Symposium on Digital Forensics and Security, ISDFS 2025 -- 24 April 2025 through 25 April 2025 -- Boston -- 209331
Keywords: artificial intelligence; augmented reality; virtual reality